2021
DOI: 10.3390/ph14121303
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Inhibitors of Kv1.5: An Option for the Treatment of Atrial Fibrillation

Abstract: The human voltage gated potassium channel Kv1.5 that conducts the IKur current is a key determinant of the atrial action potential. Its mutations have been linked to hereditary forms of atrial fibrillation (AF), and the channel is an attractive target for the management of AF. The development of IKur blockers to treat AF resulted in small molecule Kv1.5 inhibitors. The selectivity of the blocker for the target channel plays an important role in the potential therapeutic application of the drug candidate: the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 158 publications
2
16
0
Order By: Relevance
“…One method to circumvent the undesired side effects is to target ion channels which are predominantly expressed in the atria (e.g., I Kur ), although their antifibrillatory efficacy is controversial (Voigt and Dobrev, 2016;Heijman et al, 2021). Therefore, extensive efforts have been made to develop pharmacological agents that modulate atrial-specific channels (EI-Haou et al, 2015;Peyronnet and Ravens, 2019;Geng et al, 2020;Borrego et al, 2021). In the present study, we found that HMQ1611 blocked the heterologous hKv1.5 channels with the following action characteristics that: 1) HMQ1611 exerted little effect on the initial peak current amplitudes but gradually reduced the current levels during the depolarizing steps; 2) HMQ1611 attenuated the hKv1.5 current during the depolarizing step in a concentration-dependent manner; 3) hKv1.5 current declined steeply at potentials ranging from -40 mV to 0 mV during exposure to HMQ1611, which corresponds to the voltage range of channel opening; 4) the K D value derived by (k -1 )/(k +1 ) was 4.48 μM, which is close to the value of IC 50 (2.07 μM).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One method to circumvent the undesired side effects is to target ion channels which are predominantly expressed in the atria (e.g., I Kur ), although their antifibrillatory efficacy is controversial (Voigt and Dobrev, 2016;Heijman et al, 2021). Therefore, extensive efforts have been made to develop pharmacological agents that modulate atrial-specific channels (EI-Haou et al, 2015;Peyronnet and Ravens, 2019;Geng et al, 2020;Borrego et al, 2021). In the present study, we found that HMQ1611 blocked the heterologous hKv1.5 channels with the following action characteristics that: 1) HMQ1611 exerted little effect on the initial peak current amplitudes but gradually reduced the current levels during the depolarizing steps; 2) HMQ1611 attenuated the hKv1.5 current during the depolarizing step in a concentration-dependent manner; 3) hKv1.5 current declined steeply at potentials ranging from -40 mV to 0 mV during exposure to HMQ1611, which corresponds to the voltage range of channel opening; 4) the K D value derived by (k -1 )/(k +1 ) was 4.48 μM, which is close to the value of IC 50 (2.07 μM).…”
Section: Discussionmentioning
confidence: 99%
“…The Kv1.5 channel current is one of three repolarizing K + currents (I Kur , I Kr, and I Ks ) during the plateau and repolarization phases of the cardiac action potential (AP). As the Kv1.5 channel is expressed in the atria but scarcely in the ventricles of the human heart and the functional current of the channel is only detected in the atria (Ravens and Odening, 2017;Borrego et al, 2021), blockade of this channel can be expected to exert antiarrhythmic actions against re-entrant based atrial fibrillation (AF) without causing ventricular arrhythmias (e.g., torsade de pointes, TdP) (Wijesurendra and Casadei, 2019;Heijman et al, 2021). Moreover, several recent studies have revealed that the Kv1.5 channel is aberrantly expressed in numerous human cancers and plays crucial roles in cancer development (Comes et al, 2013;Comes et al, 2015;Ravens and Odening, 2017), suggesting that the Kv1.5 channel might be a potential molecular target for anticancer therapies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 I Kur is conducted by the voltagegated potassium channel Kv1.5, a well-known ion channel associated with the pathogenesis of atrial fibrillation. 27 Amiodarone is a highly lipophilic compound with a large volume of distribution (66 L/kg) that can easily diffuse through the epicardial layer due to its low molecular weight. The epicardial layer has a diffusion size restriction of 40 kDa, which allows amiodarone, which is only 645.3 Da, to diffuse through.…”
Section: Discussionmentioning
confidence: 99%
“…Although many types of atrial potassium currents are involved in atrial repolarization, the ultrarapid delayed rectifier current ( I Kur ) is the predominant current and has a selective presence in the atria, which makes it an ideal target for atrial selective therapy 26 . I Kur is conducted by the voltage‐gated potassium channel Kv1.5, a well‐known ion channel associated with the pathogenesis of atrial fibrillation 27 …”
Section: Discussionmentioning
confidence: 99%